Experiential Avoidance Mediates the Relationship between Prayer Type and Mental Health before and through the COVID-19 Pandemic - Lowe, Gabriel B. (Religions, 2022)
The practice of prayer has been shown to predict various mental health outcomes, with different types of prayer accounting for different outcomes. Considering the numerous stressors facing seminary students, which have only intensified throughout the COVID-19 pandemic, prayer may be a common coping strategy for students who study theology, spiritual growth, and leadership. The present study investigates the role that different types of prayer may have in reducing anxiety, depression, and work burnout among seminary students. Experiential avoidance is proposed as a mediator such that specific types of prayer contribute to greater spiritual and characterological formation through staying engaged in the midst of struggle. Longitudinal data was collected from 564 graduate seminary students from 17 institutions accredited by the Association of Theological Schools. Based on previous research, we hypothesized that experiential avoidance would mediate the relationship between colloquial, liturgical, meditative, and petitionary prayer types and the negative mental health outcomes of anxiety, depression, and work burnout. Results confirmed significant negative relationships between colloquial, liturgical, and meditative prayer types and all three mental health indicators, fully mediated by experiential avoidance. Petitionary prayer was not significantly related to lower levels of mental health. These results indicate that engaging in certain prayer practices may be a protective factor by facilitating experiential engagement.